Generation of myxomycete data from three discrete experiments using moist chamber cultures in a Neotropical forest - Rojas Alavarado, Carlos Alonso (2021)
The moist chamber technique is widely used in ecological research on myxomycetes. However, limited assessments on the usefulness of the technique have been carried out using empirical data. In the present study, three discrete experiments were carried out in a tropical forest in Costa Rica with the main objective of providing meaningful parameters for the design of future studies in similar environments. All three experiments showed that results could be maximized for representativeness by designing studies that purposedly target ecological components of the studied system. In a comparison of recorded data at three heights above the forest ground, a significantly higher number of records and species were observed in the higher vertical partitions, suggesting that collecting research material from the ground, in this ecological setting, reduces the probability of recording the highest species diversity. However, the ground level was associated with a high number of records and species within the genus Didymium, offering relevant information for studies targeting this genus. Similarly, based on effort, results from the present study suggest that a collecting effort designed to record system variability represents a superior cost-benefit situation for synecological studies than a more intense effort designed only for a limited spatial or temporal space, which in turn would reduce the ecological significance of the resultant data